Los tipos de cultura y su relación con la rotación organizacional - Fuchs, Rosa María (2012)
Personnel turnover is one of the great concerns in the business environment. One of the factors worth studying to avoid it is the organizational culture. This article presents a literature review and a model proposal that will address key aspects regarding personnel retention at the organizational level.